Dynamics of accumulation of lead and copper compoundsin the system «bottom sediments – bivalve mollusks» - Makarenko, Тatiana; Pyrkh, Olga; Khadanovich, Albina; Makarenko, Andrei (Journal of the Belarusian State University. Ecology, 2025)
The content of lead compounds in the bottom sediments of almost all studied aquatic ecosystems in 2019 decreased by 1.1–22.7 times compared to 2010, the copper content ‒ by 1.2–7.6 times. The reason for the decrease in the metal content in the bottom sediments of the studied reservoirs is the decrease in the anthropogenic load on the aquatic ecosystems of the studied territories. A significant decrease in the concentration of lead and copper compounds in the bottom sediments of reservoirs receiving either industrial wastewater or wastewater from the territory of city enterprises was noted. During 2019–2021, the content of lead and copper in the sediments of reservoirs continued to decrease by 1.1–6.5 times due to the transition of metal compounds into mobile forms, which are absorbed by biota or carried away by the current. In 2019, the lead content in the tissues of mollusks decreased by 5.0 times compared to the values obtained in 2010, but then in 2020 and 2021 the lead concentration increased in the same direction. The increase in the lead content in the tissues of mollusks in the period 2019–2021 indicates an increase in the bioavailability of metal forms in bottom sediments, since the lead input into the environment has significantly decreased. The difference in the copper content in the tissues of mollusks in 2010 and 2019 was 12.0 times downward. In 2020, the copper concentration decreased, but in 2021, an increase in the content of this pollutant in the soft tissues of the pearl mussel by 1.5 times was noted. The values of lead and copper accumulation coefficients in bottom sediments in the soft tissues of the pearl mussel varied within 0.01–0.41 and increased from 2019 to 2021. Lead (r= 0.84–0.88) and copper (r= 0.62–0.89) are characterized by a high degree of correlation between the concentration in bottom sediments and the tissues of mollusks.
Keywords: heavy metals; common barley; bottom sediments; water bodies; watercourses; copper; lead; accumulation coefficient; correlation coefficient